STRATEGI BERSAING USAHA AGROINDUSTRI ABON SAPI DI UD. KAMBOJA KOTA MATARAM - MARSELINA WONDA PANDAK; NI WAYAN PUTU MEIKAPASA; THERESIA SUZANNA CATHARINA; STEVANY HANALYNA DETHAN (GANEC SWARA, 2019)
The purpose of this study was to determine the competitive strategies applied to the Abon Cattle Industry in UD. Cambodia City of Mataram. The research method used is descriptive by conducting observations and interviews directly. The data obtained are qualitative data which are then analyzed using SWOT analysis. The data obtained are qualitative data which are then analyzed using SWOT analysis. Based on these factors, a scoring was performed which obtained results that showed a total IFAS score of 3.3 and a total EFAS score of 2.85 which indicated that the business position was in a position of stability (awareness IV). Furthermore, the results of the SWOT matrix analysis show a strength value of 3.25 and a weakness of (-2.75) so that the difference is 0.5. While from the external side, an opportunity score of 2.5 and a threat score (-3) was obtained so that the difference was (-0.5). the total IFAS score is 3.3 and the total EFAS score is 2.85 which indicates that the business position is in a position of stability (awareness IV). Furthermore, the results of the SWOT matrix analysis show a strength value of 3.25 and a weakness of (-2.75) so that the difference is 0.5. While from the external side, an opportunity score of 2.5 and a threat score (-3) was obtained so that the difference was (-0.5).     The results of the study show that the direction of the marketing strategy is in the awareness of ST (Strength-Threats) where the company must use all its strength to overcome all forms of threats that exist. The strategies that can be formulated include: (1) improving the quality of service to both permanent and new customers; (2) maintain good relations with customers through various kinds of promotions provided; and (3) improve product quality and increase the attractiveness of buyers by engaging in innovation in terms of taste or packaging